PENERAPAN FUZZY C-MEANS DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK PENENTUAN PENERIMA BANTUAN LANGSUNG MASYARAKAT (BLM) PNPM-MPd (Studi Kasus : PNPM-MPd Kec. Ngadirojo Kab. Pacitan) - , AZIZ AHMADI, Dra. Sri Hartati, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
PNPM Rural is a program to accelerate poverty reduction in an integrated and sustainable manner. The form of the PNPM-MPd activities is to provide direct aid to the people. Activities which will be funded through direct aid society (BLM) fund with the criteria according to the terms of PNPM-MPd, such as urgent to implement, more beneficial to the poor, the community can be done, rate of successful development and sustainability and supported by existing resources. Eligibility criteria is used to prioritize proposals that will produce a list ranking the proposals. In the ranking of the input data is qualitative data which is aid recipients criteria with weight value varying each criteria. The output system is the ranking of village activity proposal and categories of village proposal, which is whether or not the proposal to receive aid from the PNPM MPd. Grouping data using fuzzy c-means clustering method is to generate random numbers as the initial partition matrix, calculate the cluster center, calculate the objective function, and calculate the change in each matrix partitions. Iteration stop when the condition has been fulfilled, then the cluster center is obtained. Each cluster will be sorted by the proximity of data element to the center of the cluster to get the rank. of system, Through some the result was obtained which is grouping and ranking of aid proposal data. The form of cluster are influenced by the input of multiple input in the fuzzy cmeans process, such as the number of iterations, the degree, and the smallest error, but it is not affected by the objective function and the first iteration.